Developing improvement strategies for management of the Sisrè berry plant [Synsepalum dulcificum (Schumach & Thonn.) Daniell] based on end-users’ preferences in Southern Nigeria - Tchokponhoué, Dèdéou A.; Legba, Eric C.; N’Danikou, Sognigbé; Nyadanu, Daniel; Oselebe, Happiness O.; Achigan-Dako, Enoch G. (Frontiers in Sustainable Food Systems, 2023)
Synsepalum dulcificum is a valuable horticultural and lesser-known crop, famous for the uniqueness of its taste modifying properties, which is candidate for genetic improvement in West Africa. Semi-structured interviews were conducted with 100 respondents purposively selected to analyze the current production systems and constraints as well as to document the farmers’ and consumers’ preferences for breeding traits in Southern Nigeria. The results showed that none of the investigated farmers applied all required crop management practices to produce the species (land cleaning before establishment, pegging and lining, holing, base manure application, crop irrigation, weeding, pruning, fertilizers application, and pests and diseases control). Farmers were grouped into three clusters based on crop management practices. There was a strong and highly significant agreement among farmers (Kendall’s W = 0.8, p < 0.001) that bush fire, poor plant growth, drought, pests, and parasitic weed were the five most important constraints in Southwest Nigeria. In Southeast Nigeria, damage by insects and birds, poor seed germinability and poor knowledge of cultivation technics were the most important constraints challenging production. Farmers’ agreement around these constraints was moderate but highly significant (Kendall’s W = 0.6, p < 0.001). Overall, the top three desired breeding traits by farmers included: high growth rate, extended fruit shelf-life, and high fruits yield while the top three consumer’s preferences included: high miraculin potency (long lasting action of the miraculin), fruit glossiness, and high metabolites content. However, cultural specificities were detected in these preferences with a higher agreement in Yoruba farmers’ preferences compared with their counterparts Igbo. The Igbo consumers showed a higher concordance in their traits’ preferences than the Yoruba consumers. These findings pave the way for an informed cultivar development for the Sisrè berry plant in Nigeria and expand knowledge on end-users’ preferences for the species in West Africa.